Komunikasi Dalam Keluarga (Pola Asuh Orangtua Pekerja Pada Anak Remaja) - Kussanti, Devy Putri (Jurnal Public Relations (J-PR), 2022)
Communication in the family is communication that exists between parents and children, so it can be said as interpersonal communication that has strong and clear ties. In addition, communication within the family is a filtering and neutralization of communication received by children from outside. Therefore, parenting in the family plays an important role for the success of forming good attitudes and emotions in children. This type of research takes a descriptive qualitative strategy or method with in-depth interpretation so that it can be seen the results of the analysis of the parenting patterns of both working parents towards their children whose daily lives are not taken care of by their parents, analyzes how children adopt words and behaviors that are different from what their parents have taught them. these words, attitudes and behaviors are brought home.